PENGARUH METODE PEMBELAJARAN BERBASIS PROYEK DALAM PEMBUATAN PUPUK ORGANIK CAIR TERHADAP PENINGKATAN PROBLEM SOLVING SISWA SMP - Delviana vivi Bai; Yohanes Freadyanus Kasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking skills and project-based learning are implemented during the learning process in reality in students are still very low, this can be seen from student learning outcomes. This study aims to determine the effect of project-based learning methods in making liquid organic fertilizer on improving problem solving in junior high school students. This study uses a quantitative method with a one sample pretest and posttest design. The sample in this study were grade VII students of SMPN 1 Aesesa Selatan. The study was conducted during June 2025. The research instrument used was a problem-solving ability question. The results showed that the project-based learning model had a positive effect on problem solving.